Bisphosphonate use and risk of colorectal cancer: a systematic review and meta‐analysis. (20th August 2013) - Bonovas, Stefanos; Nikolopoulos, Georgios; Bagos, Pantelis
<x xml:space="preserve">Abstract</x> Aim A growing body of evidence suggests that bisphosphonates may have chemopreventive potential against colorectal cancer. Our aim was to examine this association through a meta‐analysis of observational studies. Methods A comprehensive search for relevant articles published up to October 2012 was performed, reviews of each study were conducted and data were abstracted. Prior to meta‐analysis, the studies were evaluated for publication bias and heterogeneity. Pooled relative risk (RR) estimates and 95% confidence intervals (CIs) were calculated using the random effects and the fixed effects models. Subgroup and sensitivity analyses were also performed. Results Eight large population‐based epidemiological studies (one case‐control, two nested case‐control analyses within a cohort and five cohort studies), involving more than 630 000 participants, contributed to the analysis. We found no evidence of publication bias. However, significant heterogeneity was detected among the cohort studies. The analysis revealed a significant protective association between bisphosphonate use and colorectal cancer risk (fixed RR = 0.85, 95% CI 0.80, 0.90, random RR = 0.85, 95% CI 0.75, 0.96). When the analysis was stratified into subgroups according to study design, the association was inverse in both case‐control and cohort studies, but only in the former was it statistically significant. The sensitivity analysis confirmed the stability of our results. Furthermore, we found evidence for a dose effect; Long term bisphosphonate use was associated with a 27% decrease in the risk of developing colorectal cancer as compared with non‐use (RR = 0.73, 95% CI 0.57, 0.93). Conclusion Our findings support a protective effect of bisphosphonates against colorectal cancer. However, further evidence is warranted.